Improving the monitoring mechanism of current warehouse monitoring system with weight monitoring - Lee, Wei De (2011)
Current technology used in warehouse monitoring system is RFID and Barcode;These technologies function to identify products and detect product flows stock-in and stock-out of warehouse by having sensors/ detectors installed.However, product loss is still commonly happened in the warehouse working environments.It shows the limitation of signals detection range became the lack or inadequate of monitoring mechanism for RFID and Barcode technology in securing the products.This paper presents a prototype system project for leading out alternative monitoring tool by replacing the RFlDs technology implemented in current warehouse monitoring system with mass sensor weighting scale.This prototype system is meant to test Out the potential of mass sensor in secure up the current warehouse monitoring system.